Fertility preferences among couples in Nigeria: a cross sectional study - Emmanuel Kolawole Odusina; Titilayo Ayotunde; Michael Kunnuji; Dorothy N. Ononokpono; Ghose Bishwajit; Sanni Yaya (BMC, 2020)
Abstract Background The persistently high and stalled total fertility in Sub-Saharan Africa, including in Nigeria, calls for new efforts towards fertility reduction. Most efforts on fertility desire in sub-Saharan Africa have focused either on individual men or women with little focus on couples as a unit of analysis. Moreover, the influences of different types of marriages in which couples reproduce have not been adequately explored. Therefore, this study examined fertility desires among couples in Nigeria. Methods This paper used data from the Nigeria Demographic and Health Survey (NDHS) of 2018 to assess fertility desire by marriage type among couples in Nigeria. In addition, the association between fertility desire and disparity in couples' educational attainment, place of residence, region, religion, occupation, wealth status, children ever born and contraceptive use were considered. The participants consisted of 6813 couples aged between 15-49 years. Couples' characteristics were reported using frequency and percentage distribution tables. Descriptive and logistic regression analyses were conducted. Results Overall, the study revealed that 73.8% of couples were in monogamous relationships while 26.2% were in polygynous relationships. The mean ideal number of children for men and women were 7.2 and 6.1, respectively. Also, 49.3% of the couples reported husbands desired more children, 43.9% claimed wives desired more children, while 6.8% indicated equal number of desired children among wives and husbands. The results of binary logistic regression showed that couples in polygynous relationships were 4.3 times as likely to desire more children, compared to couples in monogamous relationships (OR = 4.3; 95% CI: 3.5, 5.3). Couples in polygynous relationships wanted as many as four times the number of children desired by couples in monogamous relationships. Fertility desire was significantly higher among couples who indicated the following: either was using contraceptives (OR = 2.3; 95% CI: 1.6-3.4), both were not using contraceptives (OR = 2.8; 95% CI: 1.9, 4.1), lived in North East (OR = 2.0; 95% CI: 1.5, 2.6) and North West (OR = 1.7; 95% CI: 1.3, 2.3), both were not working (OR = 1.33, 95% CI; 1.1, 1.6) and were adherents of Islam (OR = 1.8; 95% CI; 1.5, 2.4). Conclusion These findings reflect the role of region, use of contraceptives, work status and religion in the fertility desire of couples. Implementing programmes and policies on sexual education and reproductive rights of couples and individuals may reduce high fertility desire and its adverse consequences, such as child and maternal morbidity and mortality in Nigeria.